Determination and analysis of the dispersive optical constants of some organic thin films - Yakuphanoğlu, Fahrettin; Cukurovali, A; Yilmaz, I (Elsevier, 2004)
The optical constants (refractive index n, extinction coefficient k and dielectric constant epsilon) of some organic thin films were determined using reflectance and transmittance spectra. The real part and imaginary parts of the complex dielectric constant were calculated. The analysis of the optical absorption data revealed both optical direct and indirect transition with band gaps of 2.492-2.926 and 2.07-2.13 eV, respectively. The refractive index dispersion obeyed the Single oscillator of Wemple-Didomenico model and dispersion parameters and high-frequency dielectric constant were determined. (C) 2004 Elsevier B.V. All rights reserved.
Keywords: optical constants; optical band gap; thin films